Análisis geoespacial de las características morfodinámicas de la subcuenca del río Teaone, Esmeraldas- Ecuador - Quispe Mera, Álex Gabriel (2023)
In the present work, the morphometric and functional characteristics of the Teaone river sub-basin were studied, using geographic information systemtools, as an input for land use planning. Digital global elevation models from the Advanced Spaceborne Thermal Emission and Reflection Radiometer(ASTER-GDEM) were used. Among the most outstanding parameters we have that the Teaone river sub-basin has an area of 504,66 km2, aperimeter of 138,48 km, a shape factor of 0,27; which means that it is not prone to flash floods; and a compactness index of 1,74 that expresses theelongated shape of the sub-basin, with a low water concentration and unlikely recurrent floods.